Consequences of political interference on the professionalism of the Lesotho Defence Force : Military professionalism - Masiya, Tyanai; Makhabane, Mathuso; Lubinga, Stellah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This article examines the consequences of political interference on the professionalism of the Lesotho Defence Force. Political interference has affected diverse African public institutions' smooth and professional operations. Using the qualitative research approach, the study examined the consequences of political interference on the professionalism of the Lesotho Defence Force. Data was gathered from secondary sources. The collected secondary data was analysed using thematic analysis. The identified consequences encompass the politicisation of the military, the abuse of power, compromised autonomy, erosion of meritocracy, degradation of civilian-military relations, threats to national security, and diminishing citizens’ trust. In light of these critical findings, the study advocates for decisive actions to mitigate the adverse effects of political interference. Specifically, the article recommends the comprehensive implementation of military security sector reforms aimed at fostering a transparent, accountable, and civilian-responsive military that aligns with the public's needs and operates in a manner consistent with international standards.